AN EXAMINATION OF THE EFFICACY OF ONLINE PAYMENT OF ZAKAT FITRAH BASED ON YUSUF AL-QARHDAWI’S THOUGHT - Tuddini, Nora; Abdullah, Muslim; Pannakal, Abbas (JURISTA: Jurnal Hukum dan Keadilan, 2023)
This research was conducted to find out how Zakat Fitrah payments are practiced online, and how Yusuf al-Qardhawi's opinion of Zakat fitrah legallity for being payed online. This study uses qualitative research methods with normative approaches or library research where data collection techniques are carried out by exploring theories that match the title. The results  found that paying Zakat Fitrah using both cash and online money is legitimate, because according to Yusuf Qardhawi issuing zakat fitrah through online applications with money transfers is more appropriate in our time today. Money is more practical and more useful. The money is better for the poor than the food. In addition, Yusuf Qardhawi also compared the Zakat Fitrah with the conditions of modern-day people who are more or less dependent on their needs with the money, with the condition of the people at the time of the descent of the zakat fitrah, the people of Medina who are not so familiar with the function of money.